Revised historical Northern Hemisphere black carbon emissions based on inverse modeling of ice core records - Sabine Eckhardt; Ignacio Pisso; Nikolaos Evangeliou; Christine Groot Zwaaftink; Andreas Plach; Joseph R. McConnell; Michael Sigl; Meri Ruppel; Christian Zdanowicz; Saehee Lim; Nathan Chellman; Thomas Opel; et al. (Nature Communications, 2023)
Black Carbon is an important climate forcer with poorly constraint historic emission fluxes and therefore large emission uncertainty. Here, ice-core data are combined with modelling to reconstruct historical emissions of Black carbon and finding gaps with the existing inventories, which implies potential climate sensitivity biases